“Deus é amor ou poder?”: estudo do processo de sucessão do líder religioso na Igreja Pentecostal “Deus é Amor” - Araujo, Alden Antonio de (2017)
The Pentecostal Church "God is Love", founded in 1962 by David Martins Miranda, consolidated in the Pentecostal area from the charisma of its founder-leader. Considering the idea of elective affinity, it is possible to affirm that the social, cultural, political, economic and, especially, religious context of the 1950s and 1960s favored the emergence of this charismatic leader and the formation of IPDA, which sought to consolidate in the Pentecostal area from Some identity marks proper to this church, its Internal Regulations, its World Headquarters, IPDA's option for the poorest, the restricted and selective use of the media, and the "War on Evil" worldview. These elements that constitute IPDA's identity are intended to contribute to the consolidation of David Miranda's charisma and strengthen the monopoly of its capital. From the death of the founder emerges the need to transmit the charism and a complex process of succession surrounded by tensions in regard to disputes over power